Factors influencing Singapore companies' decisions to venture overseas - Foo, Miin Huey (2014)
The objectives of the study are to identify the facilitating and constraining factors for venturing overseas, explore the degree of importance of these factors in influencing management decisions, and generate a set of recommendations which will help in the strategic decision making of Singaporean companies in this area. For ths study, data was collected from a sample of Singaporean managers representing the top 1000 companies from various industrial sectors. A questionnaire was designed and administered through the local mail system. Analyses of the collected data were conducted using appropriate statistical tools in order to respond to the three research questions of the study. A list of 17 factors that influenced managers' decisions to venture overseas were identified through the analysis procedure. The nature of differences among the perceptions of managers from the various industrial sectors were identified and the effect of managers' demographic characteristics on their perceptions were also analysed.